Coagulation and Flocculation of Bukit Tagar Sanitary Landfill Leachate using Alum and PAC - , M. Al, Mohammed; P., Agamuthu, (Malaysian Journal of Science, 2008)
Discharge of landfill leachate into the environment without proper treatment may cause severe environmental problems since they can infiltrate the soil, causing surface and ground water pollution. Leachate from Bukit Tagar Sanitary Landfill was characterized and Jar-Test trials were applied in this study to determine the optimum conditions (effective dosage, optimum pH and mixing speed) for the removal of leachate pollutants. Polyaluminium chloride (PAC) at optimum concentration of 4mL/500mL and at pH 7, with a mixing speed of 90 rpm, gave complete removal of Cd, Pb and Cu. It also reduced about 99% of Zn at the same conditions. Aluminium sulfate (alum) at optimum concentration of 8g/500mL at pH 7 and with mixing speed of 100 rpm, gave total removal of Pb and Cu and was able to reduce 98% of Cd and 94% of Zn. Reduction of turbidity, color and TSS from leachate using PAC at optimum conditions ranged from 70% to 80%, while alum at optimum conditions gave reduction of turbidity, color and TSS in the range of 63% to 78%. PAC showed a higher removal of leachate pollutants than alum, and it was able to reduce Cd, Pb, Zn and Cu to below the EQA 1974 Standard B, while alum reduced only Pb and Cu to below the EQA 1974 Standard B. Alum was not able to remove Cd and Zn to below the EQA 1974 Standard B which may require further treatment. It was also found that the treatment using PAC was cheaper by 25% compared to alum. The average estimated cost (per day) of treating 600m3 of leachate using PAC and alum, was RM1440 and RM1920, respectively.